Discovery of an intermediate nematic state in a bilayer kagome metal ScV6Sn6 - Camron Farhang; William R. Meier; Weihang Lu; Jiangxu Li; Yudong Wu; Shirin Mozaffari; Richa P. Madhogaria; Yang Zhang; David Mandrus; Jing Xia (Nature Communications)
Abstract Nematicity, spontaneous breaking of rotational symmetry, is a ubiquitous phenomenon in correlated quantum matter. Here we show a phase transition in high-quality ScV6Sn6 bilayer kagome metal at a temperature $${T}^{*}$$ T * , occurring seven Kelvins below the charge density wave transition at $${T}_{CDW}$$ T C D W , as indicated by thermodynamic, transport, and optical measurements. This emerging intermediate phase does not exhibit spontaneous time-reversal-symmetry breaking, as evidenced by zero-field Sagnac interferometry. However, it displays a strong, spontaneous in-plane anisotropy between $${T}^{*}$$ T * and $${T}_{CDW}$$ T C D W , revealed by transport and optical polarization rotation measurements. A pronounced depolarization effect detected by the Sagnac interferometer further confirms its nematic nature. Unlike AV3Sb5, this phase, alongside the recently discovered intra-unit cell nematic order at lower temperatures, presents a diverse landscape of nematicities at multiple length and temperature scales. Our findings highlight ScV6Sn6 as a prime candidate for realizing symmetry-breaking phases driven by charge density competition, kagome physics, and Van Hove singularities.